To solve for x, we need to simplify the equation and isolate the variable x.
-7x + 40 + -37
Combine like terms: 40 + -37 = 3
-7x + 3
Subtract 3 from both sides of the equation to move it to the other side:
-7x = -3
Divide both sides of the equation by -7 to solve for x:
x = -3 / -7
Simplify the fraction:
x = 3/7
Therefore, x is equal to 3/7.
Solve for x
-7x + 40 + -37
33 answers
Solve for M
m/8 - 4 = -12
m/8 - 4 = -12
To solve for M, we need to isolate the variable M on one side of the equation.
First, we add 4 to both sides of the equation to eliminate the constant -4:
m/8 - 4 + 4 = -12 + 4
This simplifies to:
m/8 = -8
Next, we multiply both sides of the equation by 8 to eliminate the denominator 8:
(8)(m/8) = -8(8)
This simplifies to:
m = -64
Therefore, M is equal to -64.
First, we add 4 to both sides of the equation to eliminate the constant -4:
m/8 - 4 + 4 = -12 + 4
This simplifies to:
m/8 = -8
Next, we multiply both sides of the equation by 8 to eliminate the denominator 8:
(8)(m/8) = -8(8)
This simplifies to:
m = -64
Therefore, M is equal to -64.
Solve for x
2/5(10x + 15) + 26
2/5(10x + 15) + 26
To solve for x, we need to simplify the expression and then isolate the variable x.
First, let's simplify the expression inside the parentheses:
10x + 15
Next, let's distribute the fraction 2/5 to the simplified expression:
(2/5)(10x + 15) = (4x + 6)
Now, we can rewrite the expression as:
(4x + 6) + 26
Combine like terms: 6 + 26 = 32
So, the expression simplifies to:
4x + 32
Now, let's isolate the variable x by subtracting 32 from both sides:
4x + 32 - 32 = 0 - 32
This simplifies to:
4x = -32
Finally, divide both sides of the equation by 4 to solve for x:
4x/4 = -32/4
This simplifies to:
x = -8
Therefore, x is equal to -8.
First, let's simplify the expression inside the parentheses:
10x + 15
Next, let's distribute the fraction 2/5 to the simplified expression:
(2/5)(10x + 15) = (4x + 6)
Now, we can rewrite the expression as:
(4x + 6) + 26
Combine like terms: 6 + 26 = 32
So, the expression simplifies to:
4x + 32
Now, let's isolate the variable x by subtracting 32 from both sides:
4x + 32 - 32 = 0 - 32
This simplifies to:
4x = -32
Finally, divide both sides of the equation by 4 to solve for x:
4x/4 = -32/4
This simplifies to:
x = -8
Therefore, x is equal to -8.
2/5(10x + 15) = 26
solve for x
solve for x
To solve for x, we need to isolate the variable x.
Let's distribute the 2/5 to the expression inside the parentheses:
2/5(10x + 15) = 26
(2/5) * 10x + (2/5) * 15 = 26
2(2x) + 2(3) = 26
4x + 6 = 26
Now, let's isolate x by subtracting 6 from both sides:
4x + 6 - 6 = 26 - 6
4x = 20
Lastly, divide both sides of the equation by 4 to solve for x:
(4x)/4 = 20/4
x = 5
Therefore, x is equal to 5.
Let's distribute the 2/5 to the expression inside the parentheses:
2/5(10x + 15) = 26
(2/5) * 10x + (2/5) * 15 = 26
2(2x) + 2(3) = 26
4x + 6 = 26
Now, let's isolate x by subtracting 6 from both sides:
4x + 6 - 6 = 26 - 6
4x = 20
Lastly, divide both sides of the equation by 4 to solve for x:
(4x)/4 = 20/4
x = 5
Therefore, x is equal to 5.
Denny bought tickets to the circus. He bought 3 child tickets. The child tickets were $5 less than the adult tickets. He spent $45 total. Which equation can be used to find the price of an adult ticket, t?(1 point)
Let's assume the price of an adult ticket is t dollars.
Since Denny bought 3 child tickets, the total amount he spent on child tickets would be 3 multiplied by the price of the child ticket, which would be t - 5 dollars.
The total amount Denny spent on the tickets is $45. Therefore, we can set up the equation:
3(t - 5) + t = 45
This equation represents the total amount Denny spent on child tickets plus the price of an adult ticket equals $45.
So, the correct equation to find the price of an adult ticket, t, is:
3(t - 5) + t = 45
Since Denny bought 3 child tickets, the total amount he spent on child tickets would be 3 multiplied by the price of the child ticket, which would be t - 5 dollars.
The total amount Denny spent on the tickets is $45. Therefore, we can set up the equation:
3(t - 5) + t = 45
This equation represents the total amount Denny spent on child tickets plus the price of an adult ticket equals $45.
So, the correct equation to find the price of an adult ticket, t, is:
3(t - 5) + t = 45
Solve for x.
50 (4x + 12) -200
50 (4x + 12) -200
To solve for x, we need to simplify the expression and then isolate the variable x.
First, let's simplify the expression inside the parentheses:
4x + 12
Next, let's distribute the 50 to the simplified expression:
50(4x + 12) = 200x + 600
Now, we can rewrite the expression as:
200x + 600 - 200
Combine like terms: 600 - 200 = 400
So, the expression simplifies to:
200x + 400
Now, let's isolate the variable x by subtracting 400 from both sides:
200x + 400 - 400 = 0 - 400
This simplifies to:
200x = -400
Finally, divide both sides of the equation by 200 to solve for x:
200x/200 = -400/200
This simplifies to:
x = -2
Therefore, x is equal to -2.
First, let's simplify the expression inside the parentheses:
4x + 12
Next, let's distribute the 50 to the simplified expression:
50(4x + 12) = 200x + 600
Now, we can rewrite the expression as:
200x + 600 - 200
Combine like terms: 600 - 200 = 400
So, the expression simplifies to:
200x + 400
Now, let's isolate the variable x by subtracting 400 from both sides:
200x + 400 - 400 = 0 - 400
This simplifies to:
200x = -400
Finally, divide both sides of the equation by 200 to solve for x:
200x/200 = -400/200
This simplifies to:
x = -2
Therefore, x is equal to -2.
50 (4x + 12) = -200 solve for x
To solve for x, let's simplify the equation by distributing 50 to the terms inside the parentheses:
50 * 4x + 50 * 12 = -200
Simplifying further:
200x + 600 = -200
To isolate the variable x, subtract 600 from both sides of the equation:
200x + 600 - 600 = -200 - 600
This simplifies to:
200x = -800
Finally, divide both sides of the equation by 200 to solve for x:
200x/200 = -800/200
This simplifies to:
x = -4
Therefore, x is equal to -4.
50 * 4x + 50 * 12 = -200
Simplifying further:
200x + 600 = -200
To isolate the variable x, subtract 600 from both sides of the equation:
200x + 600 - 600 = -200 - 600
This simplifies to:
200x = -800
Finally, divide both sides of the equation by 200 to solve for x:
200x/200 = -800/200
This simplifies to:
x = -4
Therefore, x is equal to -4.
Solve for x
1.5 - x = -4.5
1.5 - x = -4.5
To solve for x, we need to isolate the variable x on one side of the equation.
First, let's add x to both sides to eliminate -x on the left side:
1.5 - x + x = -4.5 + x
This simplifies to:
1.5 = -4.5 + x
Next, let's subtract -4.5 from both sides to move it to the other side:
1.5 - (-4.5) = -4.5 + x - (-4.5)
Simplifying the left side:
1.5 + 4.5 = -4.5 + x + 4.5
This simplifies to:
6 = x
Therefore, x is equal to 6.
First, let's add x to both sides to eliminate -x on the left side:
1.5 - x + x = -4.5 + x
This simplifies to:
1.5 = -4.5 + x
Next, let's subtract -4.5 from both sides to move it to the other side:
1.5 - (-4.5) = -4.5 + x - (-4.5)
Simplifying the left side:
1.5 + 4.5 = -4.5 + x + 4.5
This simplifies to:
6 = x
Therefore, x is equal to 6.
Solve for x
6y - 9y + 6 = -12
6y - 9y + 6 = -12
To solve for x, we need to combine like terms and isolate the variable x on one side of the equation.
First, let's combine the y terms:
6y - 9y = -3y
The equation becomes:
-3y + 6 = -12
Next, let's isolate the variable x by subtracting 6 from both sides of the equation:
-3y + 6 - 6 = -12 - 6
This simplifies to:
-3y = -18
Finally, divide both sides of the equation by -3 to solve for y:
(-3y) / -3 = (-18) / -3
This simplifies to:
y = 6
Therefore, y is equal to 6.
First, let's combine the y terms:
6y - 9y = -3y
The equation becomes:
-3y + 6 = -12
Next, let's isolate the variable x by subtracting 6 from both sides of the equation:
-3y + 6 - 6 = -12 - 6
This simplifies to:
-3y = -18
Finally, divide both sides of the equation by -3 to solve for y:
(-3y) / -3 = (-18) / -3
This simplifies to:
y = 6
Therefore, y is equal to 6.
Solve for w
15w + 3w + 19 = -17
15w + 3w + 19 = -17
To solve for w, we need to combine like terms and isolate the variable w on one side of the equation.
First, let's combine the w terms:
15w + 3w = 18w
The equation becomes:
18w + 19 = -17
Next, let's isolate the variable w by subtracting 19 from both sides of the equation:
18w + 19 - 19 = -17 - 19
This simplifies to:
18w = -36
Finally, divide both sides of the equation by 18 to solve for w:
(18w) / 18 = (-36) / 18
This simplifies to:
w = -2
Therefore, w is equal to -2.
First, let's combine the w terms:
15w + 3w = 18w
The equation becomes:
18w + 19 = -17
Next, let's isolate the variable w by subtracting 19 from both sides of the equation:
18w + 19 - 19 = -17 - 19
This simplifies to:
18w = -36
Finally, divide both sides of the equation by 18 to solve for w:
(18w) / 18 = (-36) / 18
This simplifies to:
w = -2
Therefore, w is equal to -2.
Simplify
(6x - 10) - (2x + 12)
(6x - 10) - (2x + 12)
To simplify the expression (6x - 10) - (2x + 12), we can distribute and combine like terms.
First, let's distribute the negative sign to the terms inside the second parentheses:
(6x - 10) - 2x - 12
Next, let's remove the parentheses while keeping the negative sign in front of each term:
6x - 10 - 2x - 12
Now, let's combine like terms:
(6x - 2x) + (-10 - 12)
This simplifies to:
4x - 22
Therefore, the simplified expression is 4x - 22.
First, let's distribute the negative sign to the terms inside the second parentheses:
(6x - 10) - 2x - 12
Next, let's remove the parentheses while keeping the negative sign in front of each term:
6x - 10 - 2x - 12
Now, let's combine like terms:
(6x - 2x) + (-10 - 12)
This simplifies to:
4x - 22
Therefore, the simplified expression is 4x - 22.
Jenny bought 6 cookies and 6 cupcakes at the bakery. The cookies were $1.50 each, but she cannot remember how much each cupcake was. She paid $21 total. How much was each cupcake?(1 point)
Let's assume the price of each cupcake is c dollars.
Jenny bought 6 cookies, so the cost of the cookies would be 6 multiplied by $1.50, which would be $9.
The total amount she paid, including the cost of the cookies and cupcakes, is $21. Therefore, we can set up the equation:
9 + 6c = 21
This equation represents the cost of the cookies plus the cost of the cupcakes equaling $21.
Next, let's solve for c by subtracting 9 from both sides of the equation:
9 + 6c - 9 = 21 - 9
This simplifies to:
6c = 12
Finally, divide both sides of the equation by 6 to solve for c:
6c/6 = 12/6
This simplifies to:
c = 2
Therefore, each cupcake costs $2.
Jenny bought 6 cookies, so the cost of the cookies would be 6 multiplied by $1.50, which would be $9.
The total amount she paid, including the cost of the cookies and cupcakes, is $21. Therefore, we can set up the equation:
9 + 6c = 21
This equation represents the cost of the cookies plus the cost of the cupcakes equaling $21.
Next, let's solve for c by subtracting 9 from both sides of the equation:
9 + 6c - 9 = 21 - 9
This simplifies to:
6c = 12
Finally, divide both sides of the equation by 6 to solve for c:
6c/6 = 12/6
This simplifies to:
c = 2
Therefore, each cupcake costs $2.
Half the sum of a number and 26 is 15. What is the number?(1 point)
Let's assume the number is x.
The expression "half the sum of a number and 26" can be written as (1/2)(x + 26).
According to the problem, this expression equals 15.
So, we can set up the equation:
(1/2)(x + 26) = 15
Now, let's solve for x by multiplying both sides of the equation by 2 to eliminate the fraction:
2 * (1/2)(x + 26) = 2 * 15
This simplifies to:
x + 26 = 30
Now, let's isolate the variable x by subtracting 26 from both sides of the equation:
x + 26 - 26 = 30 - 26
This simplifies to:
x = 4
Therefore, the number is 4.
The expression "half the sum of a number and 26" can be written as (1/2)(x + 26).
According to the problem, this expression equals 15.
So, we can set up the equation:
(1/2)(x + 26) = 15
Now, let's solve for x by multiplying both sides of the equation by 2 to eliminate the fraction:
2 * (1/2)(x + 26) = 2 * 15
This simplifies to:
x + 26 = 30
Now, let's isolate the variable x by subtracting 26 from both sides of the equation:
x + 26 - 26 = 30 - 26
This simplifies to:
x = 4
Therefore, the number is 4.
Four times the difference of a number and 7 is 12. What is the number?(1 point)
Let's assume the number is x.
The expression "four times the difference of a number and 7" can be written as 4(x - 7).
According to the problem, this expression equals 12.
So, we can set up the equation:
4(x - 7) = 12
Now, let's solve for x by dividing both sides of the equation by 4 to eliminate the coefficient:
(4(x - 7)) / 4 = 12 / 4
This simplifies to:
x - 7 = 3
Now, let's isolate the variable x by adding 7 to both sides of the equation:
x - 7 + 7 = 3 + 7
This simplifies to:
x = 10
Therefore, the number is 10.
The expression "four times the difference of a number and 7" can be written as 4(x - 7).
According to the problem, this expression equals 12.
So, we can set up the equation:
4(x - 7) = 12
Now, let's solve for x by dividing both sides of the equation by 4 to eliminate the coefficient:
(4(x - 7)) / 4 = 12 / 4
This simplifies to:
x - 7 = 3
Now, let's isolate the variable x by adding 7 to both sides of the equation:
x - 7 + 7 = 3 + 7
This simplifies to:
x = 10
Therefore, the number is 10.
What is the first step in solving the equation
3= 6y + 9
3= 6y + 9
To solve the equation 3 = 6y + 9, the first step would be to subtract 9 from both sides of the equation in order to isolate the term with the variable:
3 - 9 = 6y + 9 - 9
This simplifies to:
-6 = 6y
So, the first step in solving the equation is to subtract 9 from both sides to eliminate the constant term.
3 - 9 = 6y + 9 - 9
This simplifies to:
-6 = 6y
So, the first step in solving the equation is to subtract 9 from both sides to eliminate the constant term.
Simplify
2(3x + 4) - 3 (2x - 2) + 8 (x - 5)
2(3x + 4) - 3 (2x - 2) + 8 (x - 5)
To simplify the expression 2(3x + 4) - 3 (2x - 2) + 8 (x - 5), we need to distribute and combine like terms.
Let's begin by distributing the coefficients:
2 * 3x + 2 * 4 - 3 * 2x + 3 * 2 + 8 * x - 8 * 5
This simplifies to:
6x + 8 - 6x + 6 + 8x - 40
Now, let's combine like terms:
(6x - 6x + 8x) + (8 + 6 - 40)
The like terms 6x and -6x cancel each other out, leaving us with:
8x + 8 - 40
Simplifying further:
8x - 32
Therefore, the simplified expression is 8x - 32.
Let's begin by distributing the coefficients:
2 * 3x + 2 * 4 - 3 * 2x + 3 * 2 + 8 * x - 8 * 5
This simplifies to:
6x + 8 - 6x + 6 + 8x - 40
Now, let's combine like terms:
(6x - 6x + 8x) + (8 + 6 - 40)
The like terms 6x and -6x cancel each other out, leaving us with:
8x + 8 - 40
Simplifying further:
8x - 32
Therefore, the simplified expression is 8x - 32.
Write an equation and solve: Four times a number, decreased by 4 is 8.(1 point)
Let's assume the number is x.
The equation can be written as:
4x - 4 = 8
Now, let's solve for x.
We start by adding 4 to both sides of the equation:
4x - 4 + 4 = 8 + 4
This simplifies to:
4x = 12
Next, we divide both sides of the equation by 4 to solve for x:
4x/4 = 12/4
This simplifies to:
x = 3
Therefore, the number is 3.
The equation can be written as:
4x - 4 = 8
Now, let's solve for x.
We start by adding 4 to both sides of the equation:
4x - 4 + 4 = 8 + 4
This simplifies to:
4x = 12
Next, we divide both sides of the equation by 4 to solve for x:
4x/4 = 12/4
This simplifies to:
x = 3
Therefore, the number is 3.